Heteroatom-doped hierarchical porous carbons as high-performance metal-free oxygen reduction electrocatalysts1. Issue 22 (14th June 2015) - Zhu, Yun-Pei; Liu, Youlin; Liu, Yu-Ping; Ren, Tie-Zhen; Du, Gao-Hui; Chen, Tiehong; Yuan, Zhong-Yong
<x xml:space="preserve">Abstract</x> Heteroatom-doped porous carbons synthesized through a universal polymerization–carbonization protocol exhibit considerable high activity and stability towards electrochemical oxygen reduction.